River Symbolizing as Untamable Force of Nature and Freedom in Arun Joshi’s The City and the River (International Journal of Food and Nutritional Sciences, 2022)
River has ever been the vital force of life and sustenance to the land. Life has existed only where river has existed. All the civilizations of the world are grown on the river. It is the bloodline of the entire ecosystem on the Earth. River has ever been the fascinating force and balance of the nature. Man has always been dependent on this force. When there is exploitation by the egoistic and greedy man, then the nature plays its all powerful role to bring balance